Prevalence, awareness, and treatment of chronic kidney disease among adults in Yunnan Province, China: findings from the 2023 chronic disease and risk factors surveillance - Shao, Ying; Fan, Yunyuan; Gao, Jiao; Meng, Haorong; Wang, Meixian; Shi, Qingping; Chen, Yang (Frontiers in Public Health, 2025)
BackgroundBased on data from the seventh China Chronic Diseases and Risk Factors Surveillance (CCDRFS) conducted in Yunnan Province in 2023, this study aimed to provide province-wide estimates of the prevalence, awareness, and treatment of chronic kidney disease (CKD) and to describe their distribution.MethodsThis provincial-level representative cross-sectional study included 6,231 adults sampled from 10 county- or district-level surveillance sites in Yunnan Province, Southwest China. All participants were subject to questionnaires, physical examinations, and laboratory tests. CKD-EPI equation was used to estimate glomerular filtration rate (eGFR) based on serum creatinine.ResultsA total of 6,231 adults with measurements of eGFR and urine albumin were included in this study. The weighted prevalence of CKD was 13.1% (95% CI: 10.9–15.6%) overall, 12.7% (95% CI: 10.1–15.8%) among males, and 13.5% (95% CI: 10.2–17.6%) among females. Higher prevalence of CKD was observed in subgroups characterized by older age, lower education levels, being divorced/widowed/separated, and the presence of comorbidities (hypertension, diabetes, and hyperuricemia). Among participants with CKD, 61.5, 34.2, 3.2, 0.7, 0.2, and 0.1% were classified into stage G1, G2, G3a, G3b, G4, and G5, respectively. Overall CKD awareness and treatment rates were 3.0% (95% CI: 1.5–5.8%) and 1.0% (95% CI: 0.4–2.2%). Among individuals aware of their CKD status, 11.5% (95%CI: 6.5–19.9%) were receiving treatment. Participants with stage G4 or G5 demonstrated higher awareness and treatment. CKD patients with comorbid hypertension had higher awareness, while underweight CKD patients had higher treatment rates.ConclusionThe estimated CKD prevalence among adults in Yunnan Province in 2023 exceeded the national average (8.2%). CKD awareness and treatment rates were critically low. Targeted early screening programs or community-based interventions should be prioritized as urgent public health initiatives to improve disease recognition and treatment adherence for CKD prevention and management in China’s less developed regions.